Immunocorrective and Antiviral Activity of Polysaccharide from Marine Bacteria Against Tick-Borne Encephalitis Virus - N. V. Krylova; T. P. Smolina; M. V. Berlizova; G. N. Leonova (Антибиотики и Химиотерапия, 2020)
The aim of this study was to examine the immunocorrective and antiviral activity of extracellular polysaccharide (EPS) from the marine bacteria Pseudoalteromonas nigrifaciens against tick-borne encephalitis virus (TBEV). Materials and Methods. The cytotoxicity of EPS was determined in pig embryo kidney (PK) cells using the MTT test. Antiviral activity of EPS against virus TBE was evaluated in cell cultures of PK cells and human peripheral blood mononuclear cells using the methods of inhibiting the cytopathogenic effect of the virus, indirect immunofluorescence, and real-time PCR. The immunocorrective activity of EPS was investigated in whole-blood samples (from 10 healthy donors) infected with TBEV, using flow cytometry assay and enzyme immunoassay. Results. It was found that EPS is non-toxic, inhibits the TBEV replication in PK cells and mononuclear cells, significantly reduces the number of virus-infected cells and levels of viral RNA, exhibits pronounced virucidal effects (selectivity index of polysaccharide is more than 40). EPS treatment of TBEV-infected whole blood samples restored the virus-induced decline of CD69, HLA-DR and CD107a expression levels on the surface of monocytes, NK and CD8+T-cells and the pro-inflammatory cytokine production (IL-1/3, IFN-a, TNF- a, IFN-y, IL-6) by immunocompetent cells. Conclusion. The results obtained allow considering extracellular polysaccharide from marine bacteria Pseudoalteromonas nigrifaciens as a promising antiviral and immunocorrective agent against TBE infection.